Global environmental change effects on plant community composition trajectories depend upon management legacies. (18th January 2018) - Perring, Michael P.; Bernhardt‐Römermann, Markus; Baeten, Lander; Midolo, Gabriele; Blondeel, Haben; Depauw, Leen; Landuyt, Dries; Maes, Sybryn L.; De Lombaerde, Emiel; Carón, Maria Mercedes; Vellend, Mark; Brunet, Jörg; et al.
Abstract: The contemporary state of functional traits and species richness in plant communities depends on legacy effects of past disturbances. Whether temporal responses of community properties to current environmental changes are altered by such legacies is, however, unknown. We expect global environmental changes to interact with land‐use legacies given different community trajectories initiated by prior management, and subsequent responses to altered resources and conditions. We tested this expectation for species richness and functional traits using 1814 survey‐resurvey plot pairs of understorey communities from 40 European temperate forest datasets, syntheses of management transitions since the year 1800, and a trait database. We also examined how plant community indicators of resources and conditions changed in response to management legacies and environmental change. Community trajectories were clearly influenced by interactions between management legacies from over 200 years ago and environmental change. Importantly, higher rates of nitrogen deposition led to increased species richness and plant height in forests managed less intensively in 1800 (i.e., high forests), and to decreases in forests with a more intensive historical management in 1800 (i.e., coppiced forests). There was evidence that these declines in community variables in formerly coppiced forests were ameliorated by increased rates of temperature change between surveys. Responses were generally apparent regardless of sites' contemporary management classifications, although sometimes the management transition itself, rather than historic or contemporary management types, better explained understorey responses. Main effects of environmental change were rare, although higher rates of precipitation change increased plant height, accompanied by increases in fertility indicator values. Analysis of indicator values suggested the importance of directly characterising resources and conditions to better understand legacy and environmental change effects. Accounting for legacies of past disturbance can reconcile contradictory literature results and appears crucial to anticipating future responses to global environmental change. Abstract : We tested whether the temporal response of temperate forest understorey plant community properties to current environmental change depends on management legacies. Using data from nearly two thousand plots situated across Europe, we showed that stands managed as coppice in 1800 (and shown in black) had a different response to those stands managed as high forest (shown in grey) regardless of their current management. Our results can help reconcile contradictory literature findings on biodiversity and functional trait responses across time, and demonstrate the need to consider the past when projecting community responses to current environmental change.